UJI DAYA HAMBAT DAUN Harrisonia perforata Merr. TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DAN Salmonella typhi - Irna Olvaliani Aimang; Ramadhanil Ramadhanil; Syariful Anam; Ivan Ivan (Biocelebes, 2015)
Reseacrh of inhibition test of leaves extract of Harrisonia perforata Merr. against to the growth of Eschericia coli and Salmonella thypi had been conducted during period of March to May 2014. The aim of this research was to gain the effectivity of leaves extract to inhibite the growth of E. coli dan S.thypi. Maceration method was used as the extraction method and Agar Diffusion method. The research was design by Completely Randomized Design with four(4) treatments and three(3) replications (for both bacterias). The treatments were leaves extract concentrate 15% 10%, 15%, and positive control (2 mg of Ciprofloxacin for E.coli and 2 mg Cloramfenikol for S.thypi). The result showed that leaves extract of H. perforata Merr. had inhibition effect to the growth of bacterias. The extract concentrate 15% produced the biggest inhibition zone for both E. coli and S. thypi (20,9 mm and 19,3 mm repectively) than other concentrates.   Keywords : Extract concentration, Harrisonia perforata Merr., Bacterial inhibition zone, Eschericia coli, Salmonella thypi.